PEMANFAATAN SERBUK GERGAJI JEUNGJING SEBAGAI KOMPOS UNTUK PUPUK TANAMAN - Ridwan Achmad Pasaribu (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
The result of composting experiment for the manufacture of compost as fertilizer is reported in this paper. The compost was prepared from jeungjing (Albizia falcataria L. Fosberg) sawdust and rice straw using the indoors process. Jeungjing sawdust mixed with rice straw were composted for 10 days, 20 days, 35 days and 55 days. The results are as follows:Except for C/N ratio, the compost produced from different compositions of jeungjing sawdust and rice straw, contained organic carbon, total nitrogen and volume reduction of compost which were not significantly different. Organic carbon, total nitrogen, C/N-ratio and volume reduction of compost were significantly affected by composting time. A combination of 60 percent jeungjing sawdust and 40 percent rice straw composted for about 35 days, produces compost with a relatively low C/N ratio (about 45.87) and volume reduction of 15.47% The C/N ratio content was not as good as that of soils which is about 20 (Thompson, 1957).